2020
DOI: 10.4236/jfrm.2020.93012
|View full text |Cite
|
Sign up to set email alerts
|

E-Fraud in Nigerian Banks: Why and How?

Abstract: The advent of the internet and the adoption of e-payment platforms as a convenient means of payment have increased the extent of occurrence of e-fraud and cyber-attacks in Nigerian Banks. The study, therefore, investigated why and how e-frauds are perpetrated in the Deposits Money Banks in Nigeria by employees. The survey research design was adopted. Primary data were sourced from 120 fraud investigation officers in the Banks through the administration of structured questionnaires. Data were analysed using sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Despite the gains of electronic banking through automated teller machines, mobile phone USSD transactions, point of sale banking transactions and the online web transactions, Babatunde, Salawu and Adekanmi [11] suggested that the adoption of these electronic payment platforms as a convenient means of payment have increased the extent of occurrence of electronic fraud and cyber-attacks in Nigerian Banks.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the gains of electronic banking through automated teller machines, mobile phone USSD transactions, point of sale banking transactions and the online web transactions, Babatunde, Salawu and Adekanmi [11] suggested that the adoption of these electronic payment platforms as a convenient means of payment have increased the extent of occurrence of electronic fraud and cyber-attacks in Nigerian Banks.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Babatunde, Salawu and Adekanmi [11] investigated "why and how e-frauds are perpetrated in the Deposits Money Banks in Nigeria by employees. The survey research design was adopted.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Weak laws and weak policing have served as the fertile ground for fraud to thrive in Nigeria -where most internet fraudsters openly flaunt their wealth and are celebrated as role models [23,20,27,36]. This has further ensured that online fraud remains on the increase and incidences of occurrence more rampant [25,26,39,40,37].…”
Section: The Issue Of Security and Trustmentioning
confidence: 99%
“…Fraud was one of the main causes of the crisis in the Nigerian banking system, which led to the 1994 implementation of the bank consolidation program and the 1990 closure of numerous banking institutions (Kanu, 2022;Sunday-Adebayo et al, 2022). According to the NDIC financial reports for 2018, reported by Ololade et al (2020), there were 37,817 fraud cases, a 44.4% rise from the 26,182 instances that occurred in 2017. In addition, the amount that fraud engulfed also drastically increased in 2018, from N2.37bn (US$6.2m) in 2017 and N2.4bn (US$6.3m) in 2016 to N15.15bn (US$39.9m).…”
Section: Introductionmentioning
confidence: 99%